IMPACTS SANITAIRES, ÉCONOMIQUES ET ENVIRONNEMENTAUX DES FORMATIONS SANITAIRES PRIVEES - INTEGREES DANS LA ZONE DE SANTE DE KINDU. - MWENYEMALI, YEMBE; Bonny , ASSANI WAKENGE; Samuel , SUDI MUTUPEKE; Elie , NKAMBA KAPIAMBA (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
The LWAMA health centre is one of the private and integrated health facilities in the Kindu health area, which is eccentric in relation to the vast majority of its population, with low attendance due to the distance to be travelled, which is not only an obstacle to access to primary health care but also a problem of road accessibility. These situations were the basis for the creation of private structures which subsequently became part of national policy to organise curative and preventive activities for the benefit of a section of the population in this health area according to the standards. Their impact was measured using the quantitative method, which involved the collection of secondary statistical data available in the DHIS2 (District Heath Information Software). Static data on the use of curative and preventive services were collected, processed, and analysed to determine the contribution of the 3 integrated private health facilities in the SA to curative and preventive performance. The results obtained at the end of this study showed a positive impact and are of great implication, particularly in terms of the importance that the Ministry of Health attaches to the "public-private partnership for health" with a view to improving the health system and making it resilient; this state of affairs enabled us to formulate recommendations likely to remind each stakeholder of their responsibilities in this area.